Chylomicrons against light scattering: The battle for characterization. Issue 10 (19th June 2018) - Chernova, Darya N.; Konokhova, Anastasiya I.; Novikova, Olga A.; Yurkin, Maxim A.; Strokotov, Dmitry I.; Karpenko, Andrei A.; Chernyshev, Andrei V.; Maltsev, Valeri P.
Abstract : Chylomicrons (CMs) are lipoprotein particles circulating in blood and transporting dietary lipids. Optically speaking, CMs are small compared to the wavelength of visible light and widely distributed by the size and refractive index (RI). Consequently, intensity of light scattered by the CMs scales with up to the sixth power of their size, hampering simultaneous analysis of 60 and 600 nm CMs. We present an accurate method for quantitative characterization of large‐size CM subpopulation by the distributions over size and RI. For the first time the CM characteristics have been determined at a single particle level based on angle‐resolved light‐scattering measurements. We applied the developed method to 2 key processes relating to CM metabolism, namely in vivo dynamics of CMs in blood plasma after a meal and in vitro lipolysis of CMs by the lipoprotein lipase in postheparin plasma. We have observed the substantial variations in CM concentration, size and RI distributions. This opens the way for a multitude of medical applications involving screening of CM metabolism, which we exemplified by revealing large differences in CM characteristics after a 12‐hour fast between a healthy volunteer and a patient with atherosclerosis. Abstract : For the first time angle‐resolved light‐scattering approach has been applied to quantitatively characterize individual chylomicrons (CMs), lipoprotein particles circulating in blood, by the distributions over size and refractive index. The study of key processes relating to CM metabolism performed in this work and large differences in CM characteristics, revealed between a healthy volunteer and a patient with atherosclerosis, demonstrate great potential for a multitude of medical applications.